Bats Assemblage In Wind Cave Nature Reserve - Julius, William Dee (Universiti Malaysia Sarawak, (UNIMAS), 2014)
A species diversity study of chiropteran was conducted at the limestone cave of Wind Cave Nature Reserve (WCNR) using harp traps, mist nets and hand-net. A total of 296 individuals from 22 species and six families were recorded in this study. The most abundance species recorded was Penthetor lucasi, with 138 individuals followed by Hipposideros cervinus (49 individuals). P. lucasi and H. cervinus comprised 46% and 16% of the total individuals caught respectively. Megaderma spasma was caught using hand-net while roosting in the cave. New record for WCNR, namely Kerivoula papillosa, Myotis montivagus, M. ater, Nycteris tragata, M. spasma, H. ater, and H. bicolor making it 26 species known inhabited WCNR.